Iron chelation therapy and thalassemia - an overview. - Chakraborty, P; Rudra, S; Hossain, MA; Bhuiyan, MR; Khaleque, MA; Haque, MM (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Jul;20(3):513-519 The abstract of this article is available on the PubMed website